A rare seen case with homozygosity for pericentric inversion of chromosome 9 and primary infertility - Ceylan, Gulay; Ceylan, Cavit; Yuce, Huseyin (Int Scientific Information, Inc, 2008)
Background: Pericentric inversions of chromosome 9 are the most common pericentric inversions in humans. We investigate if there is an association between primary infertility and homozygosity for pericentric inversion of chromosome 9 and perform a search on recent literature. Case Report: The patient applied our laboratuary because of primary infertility and oligozoospermia. Convantional cytogenetic analysis and Y chromosome microdeletions screening were performed fort the patient. At the end of the convantional cytogenetic analysis and Y chromosome microdeletions screening, homozygosity for pericentric inversion of chromosome 9 and no microdeletion for Y chromosome was found, respectively. Conclusions: Although pericentric inversion of chromosome 9 is thought to be a normal chromosomal variant, homozygosity for pericentric inversion of chromosome 9 can be the cause of primary infertility.
Keywords: primary infertility; pericentric inversion; cytogenetics; oligoasthenospermia